(untitled) (Global Journal of Management and Business Research, 2018)
The turbulent challenges faced by Telecom companies in Kunming, China are to enhance their performance in the successful completion of projects to a level more satisfactory to clients. The main objective of this study is to investigate the relationship of HRM practices, Human capital and organizational performance with the mediating role of knowledge management on the successful completion of research task. The main aim of this study is to analyze the association among Human capital, HRM practices and organizational performance while taking Knowledge management as mediating variables. The survey of this research was conducted on managerial level employees who are working in Telecom companies in Kunming, China. It is hoped that current study resolve provide a guide and roadmap for employees to carry their services in their companies where fruitful plan of human resource management practices and human capital with the mediating effect of knowledge management capabilities to get the desired outcomes in human resource management. Statistical Package for the Social Sciences (SPSS) to analyze the data, Statistical tests like Cronbach’s alpha to check the reliability, correlation, confirmatory factor analysis (CFA) & regression to prove the hypotheses will apply on data.